2005
DOI: 10.1128/mcb.25.24.10684-10694.2005
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Coactivates PDK4 Gene Expression via the Orphan Nuclear Receptor ERRα: a Mechanism for Transcriptional Control of Muscle Glucose Metabolism

Abstract: The transcriptional coactivator PGC-1␣ is a key regulator of energy metabolism, yet little is known about its role in control of substrate selection. We found that physiological stimuli known to induce PGC-1␣ expression in skeletal muscle coordinately upregulate the expression of pyruvate dehydrogenase kinase 4 (PDK4), a negative regulator of glucose oxidation. Forced expression of PGC-1␣ in C 2 C 12 myotubes induced PDK4 mRNA and protein expression. PGC-1␣-mediated activation of PDK4 expression was shown to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
313
3
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(348 citation statements)
references
References 60 publications
(95 reference statements)
25
313
3
7
Order By: Relevance
“…These indicated that the PDK4 may play an important role in the skeletal muscle. It was reported that PDK4 was activated by PGC-1a via the ERRa [17,18] and skeletal-musclespecific overexpression of PGC-1a could result in a fiber type switch from fast-twitch (type II) to slow-twitch (type I) oxidative fibers [19]. These suggested that the PDK4 activated by PGC-1a may be one of the reasons that Meishan had more slow-twitch oxidative fibers than Yorkshire.…”
Section: Discussionmentioning
confidence: 99%
“…These indicated that the PDK4 may play an important role in the skeletal muscle. It was reported that PDK4 was activated by PGC-1a via the ERRa [17,18] and skeletal-musclespecific overexpression of PGC-1a could result in a fiber type switch from fast-twitch (type II) to slow-twitch (type I) oxidative fibers [19]. These suggested that the PDK4 activated by PGC-1a may be one of the reasons that Meishan had more slow-twitch oxidative fibers than Yorkshire.…”
Section: Discussionmentioning
confidence: 99%
“…(2007) and drives the transcription of genes involved in fatty acid metabolism (such as CD36, CPT1, MCAD) in order to cope with excess provision of lipids from the circulation, and of PDK4 (Wende et al. 2005), which further suppresses glucose oxidation by decreasing PDH activity (Wu et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidences indicate that another ERR subtype, ERRa, plays significant roles in energy metabolism and mitochondrial biogenesis in certain target cells and tissues via direct regulation of genes involved in fatty acid oxidation, ERRb suppresses prostate cancer cell growth S Yu et al glucose metabolism, oxidative phosphorylation and mitochondrial fusion Huss et al, 2004;Schreiber et al, 2004;Wende et al, 2005;Soriano et al, 2006;Villena et al, 2007). Moreover, ectopic ERRa expression can promote lipid accumulation in primary cardiac myocytes (Huss et al, 2004), whereas its loss of function reduces body fat in ERRa-knockout mouse (Luo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%